Status and biology of ringed seals (Phoca hispida) in Svalbard - Lydersen, Christian (NAMMCO Scientific Publications, 1998)
The ringed seal is the most abundant mammal in the Svalbard area. Annual pup production in this area is estimated to be 20,000. No systematic harvest records exist, but some few hundred seals are taken annually, mainly for dog food. The ringed seals in Svalbard are protected from hunting in the period 15 March - 15 April. Peak pupping season is the first week of April. New-born ringed seals weigh an average of 4.6 kg. They are nursed for about 39 days, and weaned at an average body mass of around 22 kg. During the period of maternal care pups consume a total of about 54 litres of milk, that is composed of approximately 38% fat and 10% protein. Asymptotic standard lengths and body masses for adult ringed seal males and females are 131.5 and 127.8 cm, and 52.6 and 59.9 kg, respectively. The maximum values recorded for lengths of males and females in Svalbard are 157 cm and 107 kg, respectively. There is marked seasonal variation in body mass in both sexes with the highest mass records being recorded in early spring before pupping occurs, and with minimum values in the summer after the breeding and moulting seasons. The observed variation in mass is mainly due to changing blubber thickness of the seals. Ringed seal males attain sexual maturity at the age of 5 - 7 years, while females reach maturity when they are 3-5 years of age. The oldest seal collected in Svalbard was aged 45. Ringed seals in the Svalbard area feed on a variety of prey organisms, the most important of which are polar cod (Boreogadus saida) and the crustaceans Parathemisto libellula, Thysanoessa inermis and Pandalus borealis. Ringed seal pups start diving during the nursing period while they are still white-coats, and spend about 50% of the time in the water prior to weaning. They are capable of diving for up to 12min and dive to the bottom of the study areas (max. 89 m). Nursing females spend more than 80% of their time in the water. Maximum recorded dive duration for mothers was 21.2 min. In order to produce a weaned pup, the net energy expenditure for a ringed seal mother is 1,073 MJ. This energy value corresponds to the consumption of 185 kg of polar cod or 282 kg of P. libellula. The annual gross energy consumption for adult males and females is calculated to be 5,600 MJ and 7,300 MJ, respectively. The main predators of ringed seals in Svalbard are polar bears (Ursus maritimus) and Arctic foxes (Alopex lagopus). In addition, both glaucous gulls (Larus hyperboreus) and walruses (Odobenus rosmarus) are documented as predators of ringed seals in this area. Heavy predation pressure is probably the main factor explaining why pups of this species start diving at such a young age, why they have access to so many breathing holes (8.7 on average) and why they keep their white coat long after its thermoregulatory properties have vanished. Pollution levels in ringed seals from Svalbard are, generally speaking, similar to levels in other areas of the Arctic.